Hazard Scenarios Related to Submarine Volcanic-Hydrothermal Activity and Advanced Monitoring Strategies: A Study Case from the Panarea Volcanic Group (Aeolian Islands, Italy). (13th October 2019) - Romano, Davide; Gattuso, Alessandro; Longo, Manfredi; Caruso, Cinzia; Lazzaro, Gianluca; Corbo, Andrea; Italiano, Francesco
Abstract : Geohazards associated to submarine hydrothermal systems still represent a tricky enigma to face and solve for the scientific community. The poor knowledge of a submarine environment, the rare and scarce monitoring activities, and the expensive and sometimes complicated logistics are the main problems to deal with. The submarine low-energy explosion, which occurred last November 3, 2002, off the volcanic island of Panarea, highlighted the absence of any hazard scenario to be used to manage the volcanic crisis. The " unrest " of the volcanic activity was triggered by a sudden input of deep magmatic fluids, which caused boiling water at the sea surface with a massive CO2 release besides changes in the fluids' geochemistry. That event dramatically pushed scientists to develop new methods to monitor the seafloor venting activity. Coupling the information from geochemical investigations and data collected during the unrest of volcanic activity, we were able to (a) develop theoretical models to gain a better insight on the submarine hydrothermal system and its relationships with the local volcanic and tectonic structures and (b) to develop a preliminary submarine volcanic hazard assessment connected to the Panarea system (Aeolian Islands). In order to mitigate the potential submarine volcanic hazard, three different scenarios are described here: (1) ordinary hydrothermal venting, (2) gas burst, and (3) volcanic eruption. The experience carried out at Panarea demonstrates that the best way to face any submarine volcanic-hydrothermal hazard is to improve the collection of data in near real-time mode by multidisciplinary seafloor observatories and to combine it with periodical sampling activity.